Relativity from the geometrization of Newtonian dynamics. (18th March 2019) - Friedman, Y.; Scarr, T.
Abstract: Based on the Generalized Principle of Inertia, which states that: An inanimate object moves freely, that is, with zero acceleration, in its own spacetime, whose geometry is determined by all of the forces affecting it, we geometrize Newtonian dynamics for any conservative force. For an object moving in a spherically symmetric force field, using a variational principle, conservation of angular momentum and a classical limit, we construct a metric with respect to which the object's worldline is a geodesic. For the gravitational field of a static, spherically symmetric mass, this metric is the Schwarzschild metric. The resulting dynamics reduces in the weak-field, low-velocity limit to classical Newtonian dynamics and exactly reproduces the classical tests of general relativity. We propose a method to extend the theory to handle a gravitational field generated by several sources.